Penerapan Hukum Terhadap Anak Sebagai Tindak Pidana Pencurian dengan Kekerasan - Ahmad Yasir Lubis; Mellisa Fadhilah Pakpahan (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study employed a socio-juridical research method, as it is well suited to the research objectives, which emphasize the normative aspects of law. The normative approach was chosen because it analyzes legal issues based on statutory regulations, including not only the Indonesian Criminal Code (KUHP) but also other laws related to the juvenile justice system and child protection. The rapid development of technology and information has significantly influenced changes in societal behavior. While these developments have generated positive impacts, such as improving efficiency and enabling people to work more effectively with advanced technologies, they have also contributed to negative behavioral changes within society. This research examines the implementation of legal provisions concerning juvenile offenders who violate Article 362 of the Indonesian Criminal Code, which regulates the crime of theft, with a case study conducted in the City of Medan. The study adopted a socio-juridical approach by combining normative legal analysis with empirical observations to examine the application of laws governing juvenile justice and child protection.The findings indicate that: (1) the primary factors contributing to theft committed by juveniles are economic hardship, environmental influences, and peer association; (2) the resolution of theft cases involving juveniles is primarily carried out through mediation and diversion, while repeat offenders (recidivists) are processed through the court system in accordance with Law No. 11 of 2012 on the Juvenile Criminal Justice System; and (3) following the court's decision, juvenile offenders are placed in the Medan Juvenile Special Development Institution (LPK) to serve one-third of their imposed sentence while receiving vocational training and skills development programs aimed at rehabilitation.